Evaluasi Ketahanan Beberapa Mutan Jagung Manis (Zea Mays L. Saccharata) Generasi M3 Terhadap Penyakit Penting - Siti Nurkholizah; Muhammad Syafi’i; Tatang Surjana (Peneliti.net, 2021)
The intensive development of maize in Indonesia has resulted in the emergence of various problems, both a decrease in productivity and yield quality. One way to get high quality maize seeds and superior varieties is by selecting the cultivation of several strains resulting from gamma irradiation which is the most widely used mutagen in producing mutant varieties.This research was carried out from August, September and October 2020 in the experimental garden of the Center for Forecasting Plant Pest Organisms (BBPOPT). The research method used a randomized block design (RAK) with a single factor repeated 9 times. The treatments used 10 sweet corn mutants consisting of treatments G1M1, G2M1, G3M2, G4M1, G5M3, G6M1, G7M3, G8M2, G9M1, G10M0. The data obtained were analyzed using variance and if the results were significantly different, it was continued with the DMRT (Duncan Multiple Range Test) test at the 5% level.The results showed that there was a significant effect on the resistance level of the sweet corn mutant (Zea mays l. saccharata) against downy mildew and leaf spot in the m3 generation. In addition, there is a sweet corn mutant genotype that has the highest resistance level, namely leaf spot disease in G1M1 treatment of 5.33%, significantly different from G6M1 treatment of 17.30% but not significantly different from other treatments. While downy mildew in G1M1 treatment was 3.75% significantly different from G10M0 treatment by 21.75% but not significantly different from other treatments